An Overview of Present Status and Future Prospects of the Tourism Sector in Bangladesh - Md Lutfur Rahman,; S M Nawshad Hossain,; Sania Sifat Miti,; A K M Abul Kalam, (Journal of Bangladesh Institute of Planners, 2010)
Bangladesh is bestowed with beautiful coasts and beaches, archeological sites, historical and religious places, hills and islands, forests and jungles and attractive countryside with innumerable water bodies and green fields of agriculture. These rich natural and cultural attractions are valuable ingredients for tourism development in Bangladesh. Every year, a large number of tourists visit these attractive places, which has a significant contribution in the national economy. However, tourism industry in Bangladesh is faced with many problems, such as lack of good transportation and communication system, lack of well planned accommodation, food, entertainment and other services to satisfy diverse categories of tourists. The issue of safety and security of the tourists of both domestic and foreign origins is also very important for the development of tourism in Bangladesh. Though a policy has been adopted in the recent time for ensuring sustainable development of this sector, the strategies adopted under the policy are not yet being seriously taken up for implementation. Besides, the country requires a strong physical planning strategy to develop its urban and rural areas, and national transportation and communication system to establish connectivity to the tourism spots. There should be a strong marketing policy as well for the promotion of tourism in the country. Thus if necessary policies, strategies and actions are taken by the national government, tourism may become a potential economic sector. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 65-75